Synthesis of a new HYNIC-DAPI derivative for labelling with 99mTechnetium and its in vitro evaluation in an FRTL5 cell line. Issue 5 (13th May 2015) - Ferl, Sandra; Wunderlich, Gerd; Smits, René; Hoepping, Alexander; Naumann, Anne; Kotzerke, Jörg
<x xml:space="preserve">Abstract</x> A new multifunctional compound that includes the fluorescent dye 4′, 6-diamidine-2-phenylindole (DAPI) and the chelator 6-hydrazinonicotinic acid (HYNIC) was developed and radiolabelled with 99mTc for in vitro evaluation in an FRTL5 cell line.